Four-week IgE/baseline IgE ratio combined with tryptase predicts clinical outcome in omalizumab-treated children with moderate-to-severe asthma - Lu Min; Zhao Jing; Zeng Mei; Zhu AiMin; Li JinFen (Open Medicine)
The aim of this study was to investigate the feasibility of the 4-week IgE/baseline IgE ratio and tryptase to predict the clinical efficacy of omalizumab in the treatment of pediatric moderate-to-severe asthma.